Conflict relations in the native communities of the province of Yauli.18th-19th centuries - Gomez Solano, Cristhian Manuel (2024)
Conflicts involving peasant communities in mining areas are currently recurring in Peru. These have ancient antecedents, as is the case of the province of Yauli, where mining activity has been practiced since the 18th century. The objective of this work is to characterize the conflict relationships, starting with the arrival of mining activity in the area. This paper was carried out through case studies and the review of, mainly, documentation for land disputes, existing in the archives of the peasant communities of the province of Yauli. It is concluded that, in this mining province, during the 18th and 19th centuries, conflict relationships were configured that can be characterized —according to the actors involved and the identities resulting from the social phenomenon— as intra-communal, inter-communal and extra-communal. Likewise, socio-economic and ethnic differentiations, which are not mutually exclusive, have been identified since the 18th century within indigenous communities.